2023
DOI: 10.3390/medicina59050855
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Analgesia with Local Wound Infiltration and Intravenous Parecoxib for Thyroidectomy

Abstract: Background and objective: Adequate postoperative pain control is an important component to enhance recovery. Multimodal analgesia with various pain control techniques has been widely used to alleviate postoperative pain. The use of either wound infiltration or a superficial cervical plexus block has been reported to be effective for pain management after thyroid surgery. The present study evaluated the effect of multimodal analgesia using lidocaine wound infiltration combined with intravenous parecoxib for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Apart from the fact that no difference regarding age between groups existed, no further age-subgroup analysis was conducted [ 3 , 4 , 5 , 6 , 10 , 11 , 16 , 17 , 18 , 19 ]. An ASA status of I or II was required when participating in the trial [ 5 , 8 , 9 , 10 , 13 , 14 , 16 , 17 , 18 , 19 ], although some authors include patients with a status of III [ 6 , 11 , 20 ]. Long-term analgesic, corticosteroid or sedative medication or the use of analgesics 7 days prior to the procedure was prohibited [ 7 , 9 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from the fact that no difference regarding age between groups existed, no further age-subgroup analysis was conducted [ 3 , 4 , 5 , 6 , 10 , 11 , 16 , 17 , 18 , 19 ]. An ASA status of I or II was required when participating in the trial [ 5 , 8 , 9 , 10 , 13 , 14 , 16 , 17 , 18 , 19 ], although some authors include patients with a status of III [ 6 , 11 , 20 ]. Long-term analgesic, corticosteroid or sedative medication or the use of analgesics 7 days prior to the procedure was prohibited [ 7 , 9 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…TSH, cortisol, renin and ACTH plasma levels, although elevated, show no difference between the groups [ 5 ]. The efficacy of lidocaine as a part of a multimodal protocol though, was also suggested by Gau et al The authors also showed that the higher volume of lidocaine was superior in terms of pain score on the day of operation and even during the first postoperative week [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations